Bortezomib induces DNA hypomethylation and silenced gene transcription by interfering with Sp1/NF-κB–dependent DNA methyltransferase activity in acute myeloid leukemia - Liu, Shujun (American Society of Hematology, 2008)
Bortezomib reversibly inhibits 26S proteasomal degradation, interferes with NF-κB, and exhibits antitumor activity in human malignancies. Zinc finger protein Sp1 transactivates DNMT1 gene in mice and is functionally regulated through protein abundance, posttranslational modifications (ie, ubiquitination), or interaction with other transcription factors (ie, NF-κB). We hypothesize that inhibition of proteasomal degradation and Sp1/NF-κB–mediated transactivation may impair aberrant DNA methyltransferase activity. We show here that, in addition to inducing accumulation of polyubiquitinated proteins and abolishment of NF-κB activities, bortezomib decreases Sp1 protein levels, disrupts the physical interaction of Sp1/NF-κB, and prevents binding of the Sp1/NF-κB complex to the DNMT1 gene promoter. Abrogation of Sp1/NF-κB complex by bortezomib causes transcriptional repression of DNMT1 gene and down-regulation of DNMT1 protein, which in turn induces global DNA hypomethylation in vitro and in vivo and re-expression of epigenetically silenced genes in human cancer cells. The involvement of Sp1/NF-κB in DNMT1 regulation is further demonstrated by the observation that Sp1 knockdown using mithramycin A or shRNA decreases DNMT1 protein levels, which instead are increased by Sp1 or NF-κB overexpression. Our results unveil the Sp1/NF-κB pathway as a modulator of DNA methyltransferase activity in human cancer and identify bortezomib as a novel epigenetic-targeting drug.